Анализ технологии предварительной обработки данных при аутентификации пользователей компьютерных систем по клавиатурному и рукописному почеркам - Высоцкая, Е.А.; Давиденко, А.Н. (Моделювання та інформаційні технології, 2010)
In this article the stages of formation of a database of educational
samples at the authentification on keyboard handwriting and at the authentification on
hand-written handwriting are submitted. The stages of preprocessing of analyzable
analyzed data at the specified two kinds of authentification are stated. The necessity of
such processing is argued.